2019
DOI: 10.9734/jeai/2019/v33i530153
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Physical Quality of the Yellow Passion Fruit under Spacing within Plants and Water Salinity

Abstract: Aims: The aim of this work was to evaluate the yield and the physical quality of the yellow passion fruit accession ‘Guinezinho’ as a function of the within-row plant spacing, with saline irrigation water in consecutive growing seasons. Study Design: The experiment was arranged in randomized blocks, with four replicates and 12 plants per parcel, in a 4 x 2 factorial arrangement, referring to the spacing in the planting lines of 3, 6, 9 and 12 m, and two consecutive growing seasons. Place and Durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The principal producing areas of passion fruit in the North-east are located in semi-arid regions and the water used for irrigation typically has high salt concentrations (Macedo et al 2019), which can impair the physical and chemical characteristics of the soil and thus affect the growth and development of crops (Brito et al 2014;Gadelha et al 2017). The high electrical conductivity of the soil and groundwater in various producing areas hinders the formation of seedlings and establishment of passion fruit crops (Cavalcante et al 2009;Bezerra et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal producing areas of passion fruit in the North-east are located in semi-arid regions and the water used for irrigation typically has high salt concentrations (Macedo et al 2019), which can impair the physical and chemical characteristics of the soil and thus affect the growth and development of crops (Brito et al 2014;Gadelha et al 2017). The high electrical conductivity of the soil and groundwater in various producing areas hinders the formation of seedlings and establishment of passion fruit crops (Cavalcante et al 2009;Bezerra et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Andrade et al (2018) evaluated physiological and growth aspects in the seedlings of two varieties of yellow passion fruit and observed that inhibition of germination was affected by high levels of salinity in irrigation water. Macedo et al (2019) also evaluated the yield and physical fruit quality of yellow passion fruit under saline conditions and found that the irrigation with highly saline water did not compromise the productive capacity. Since many of these studies have only evaluated the morphophysiological and agronomic responses of plants grown from seeds and irrigated with brackish water, there is little information on the behavior of passion fruit plants propagated asexually (via cuttings) under saline conditions (Moura et al 2019).…”
Section: Introductionmentioning
confidence: 99%